2005
DOI: 10.1111/j.1365-2982.2005.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor patterns and propulsion in the rat intestine in vivo recorded by spatio‐temporal maps

Abstract: We have used spatio-temporal maps derived from video images to investigate propagated contractions of the rat small intestine in vivo. The abdomen, including an exteriorized segment of jejunum, was housed in a humid chamber with a viewing window. Video records were converted to spatio-temporal maps of jejunal diameter changes. Intraluminal pressure and fluid outflow were measured. Contractions occupied 3.8 +/- 0.2 cm of intestine and propagated anally at 3.1 +/- 0.2 mm s(-1) when baseline pressure was 4 mmHg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…In mammals, it has been shown that ripples have a similar frequency to slow waves observed in the smooth muscles of the gastrointestinal tract, ranging between 2 and 30 cpm depending on the species and region of the gastrointestinal tract (Berčík et al, 2000;Ferens et al, 2005;Kobayashi et al, 1996;Yoneda et al, 2002). Slow waves are generated by the ICC, which act as pacemakers in the mammalian gut (Huizinga et al, 1995;Sanders, 1996;Sanders et al, 2006;Ward et al, 2004).…”
Section: Do Myogenic Ripples Represent Slow Wave Activity?mentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, it has been shown that ripples have a similar frequency to slow waves observed in the smooth muscles of the gastrointestinal tract, ranging between 2 and 30 cpm depending on the species and region of the gastrointestinal tract (Berčík et al, 2000;Ferens et al, 2005;Kobayashi et al, 1996;Yoneda et al, 2002). Slow waves are generated by the ICC, which act as pacemakers in the mammalian gut (Huizinga et al, 1995;Sanders, 1996;Sanders et al, 2006;Ward et al, 2004).…”
Section: Do Myogenic Ripples Represent Slow Wave Activity?mentioning
confidence: 99%
“…Often, different patterns dominate in different regions of the gut, but this may also depend on the fed state of the animal (Ailiani et al, 2009;Berthoud et al, 2002;Bogeski et al, 2005;Chen et al, 2013;D'Antona et al, 2001;Ferens et al, 2005;Hennig et al, 1997;Hennig et al, 1999;Hennig et al, 2010). Mixing and propulsion can be achieved by either non-propagating (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Loss or disruption of ICC networks has been linked with many gastrointestinal disorders (Ward and Sanders, 2001). Much is known about the network behaviour of mammalian ICC as a result of direct investigations utilizing c-kit (the proto-oncogene encoding the receptor tyrosine kinase, Kit; Huizinga et al, 1995;Ward et al, 1994) and Ca 2+ indicators (Hennig et al, 2004); however, indirect studies of ICC behaviour via the analysis of myogenically mediated motor behaviours have also significantly contributed to our understanding of the role of ICC (Bercik et al, 2000;D'Antona et al, 2001;Ferens et al, 2005;Hennig et al, 2010a;Kobayashi et al, 1996;Yoneda et al, 2002). ICC were originally described over a century ago, as small fusiform or stellate cells with prominent varicose processes that formed networks in gastrointestinal tissues (Cajal, 1911).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that the stresses applied by the internal magnet to the underlying tissue were within a safe range, the 1-4 mN intermagnetic force experienced by the tissue was normalized by the 2 mm 2 cross-sectional area of contact with the magnetic pill yielding localized stress of 0.5-2 kPa. The local stress imparted by magnetic pill localization corresponds to pressures ranging from 4-16 mmHg indicating that pressures experienced by the tissue during retention are within the normal physiological range for rat jejunal tissue (28). Pressures experienced by the GI region of interest are excellent guidelines for the range of safe tissue stresses imparted by localization of a magnetic pill because the tissue is naturally exposed to pressure cycling in that range (28).…”
Section: Resultsmentioning
confidence: 99%
“…The local stress imparted by magnetic pill localization corresponds to pressures ranging from 4-16 mmHg indicating that pressures experienced by the tissue during retention are within the normal physiological range for rat jejunal tissue (28). Pressures experienced by the GI region of interest are excellent guidelines for the range of safe tissue stresses imparted by localization of a magnetic pill because the tissue is naturally exposed to pressure cycling in that range (28).…”
Section: Resultsmentioning
confidence: 99%